Views from the streets : the transformation of gangs and violence on Chicago's South Side - Aspholm, Roberto R. (Studies in transgression., 2020)
"High levels of homicide and other violent crime persist in Chicago in spite of every effort to address them, confounding law enforcement and elected officials and challenging the viability of violence reduction strategies. Views from the Streets offers insights into these dynamics, exploring recent transformations in the entrenched gang culture and the nature of the gang violence that plagues Chicago's communities, analyzing the shortcomings of current approaches to addressing these issues, and providing recommendations for moving efforts to reduce violence in more promising directions. Based on eight years of ethnographic involvement, Roberto Aspholm details the context, nature, and aftermath of the internal rebellions that effectively shattered the cross-neighborhood, corporate-style African American street gangs that ruled the streets of Chicago's South Side during the 1990s. These insurrections were precipitated by a number of historical changes taking shape around the dawn of the millennium, including the decline of the crack cocaine economy, the demolition of the city's public housing projects, and the prosecution of scores of gang leaders. These developments weakened the organizational capacity of Chicago's black street gangs and laid bare their exploitative and coercive nature to their rank-and-file members, who responded by waging often-violent rebellions against their leaders. Ironically, the same impulse of resistance that compelled these young men into gangs to begin with also fueled these rebellions, as gang members' struggles to resist economic marginality, physical insecurity, and racialized social exclusion through gang involvement transformed into struggles to resist the oppressive structures and practices within their gangs"--